THE ENHANCEMENT OF ISLAMIC MORAL VALUES THROUGH SEX EDUCATION FOR EARLY CHILDREN IN THE FAMILY ENVIRONMENT - Muqarramah Sulaiman Kurdi; Yusmicha Ulya Afif (Universitas Pendidikan Indonesia, 2021)
The fast-moving conditions and development of the times, the easy access to mass media at every level requires that parents provide their children with an education. The education aimed at is sex education for children of an early age. The increasing problem of sexual deviancy behavior in the country of Indonesia is that one is the result of a lack of understanding about sexual education. Sex education should certainly be applied at an early age in order to have good morals and not be susceptible to promiscuity. Premature age is a golden phase for children, treatment of them can affect their life into adulthood. The purpose of research is to learn the importance of sexual education in an early-age child morals based on islamic religious views. A research approach uses a qualitative approach for case study methods. Studies reveal sexual education should be given concurrently with a religious basis. Child sexual education needs to be applied by family members as a protection for their child.